Solving the Powertrain Puzzle: 10th Schaeffler Symposium April 3/4, 2014 (2014)
There are plenty of technical ideas for the drive systems to power future genera- tions of vehicles. But which of these is the right solution for which application? How will the markets change in the future? What basic innovations can we use to make engines and transmissions even more efficient? At the 10th Schaeffler Symposium, 2014, we will venture a glimpse into the distant future – beyond 2020, when the most world‘s most stringent fuel consumption standards come into force in Europe. In the tradition of the Symposium, we will, on the one hand, be presenting our evolutionary technologies, which can make a significant contribution to optimizing the drive system. On the other hand, we will be discussing our radical innovations: Hybrid concepts for 48-volt on-board electric systems or a transmission concept with electric power splitting as well as electric wheel hub drives for passenger cars. We are convinced that the challenges of the future can only be overcome if per- manent further development of conven- tional powertrains based on internal com- bustion engines, and the courage to realize new ideas for electrification go hand in hand. As a supplier, we focus more than ever on people‘s changing behavior with regard to mobility, because public accep- tance will ultimately decide if and which technologies become established on the market. In this spirit, we hope you will have exciting discussions about an exciting topic: The automotive drive systems of the future!